Rickets with Alopecia Signals Vitamin D Dependent Rickets Type II - Yadav, Shankar Prasad; Bhatta, Nisha Keshary (Journal of Nepal Paediatric Society, 2016)
Vitamin D-dependent rickets type II is a rare autosomal recessive disorder. We report 27 months female child with classical rachitic changes, very high level of 25-hydroxy Vitamin D, 1,25 (OH)2D and markedly elevated serum Alkaline phosphatase. Very high dose of oral calcium and vitamin D3 was prescribed with minor improvement in skeletal features and alopecia. This case report hints the physician to diagnose and manage Vitamin D-dependent rickets type II, when rachitic changes are associated with alopecia. J Nepal Paediatr Soc 2015;35(2):198-201